Persepsi Mahasiswa Ilmu Komunikasi Universitas 17 Agustus 1945 Surabaya Mengenai Komunikasi Gender - Irmasanthi Danadharta; Dewi Sri Andika Rusmana (LPPM STIKOM Tunas Bangsa, 2023)
The purpose of this research is to understand the perceptions of Universitas 17 Agustus 1945 Surabaya Communication Students on Gender Communication. In this research, the Gender Communication will focus on the voice, bodies and language on men and women. The method of this research is Descriptive Quantitative. This research’s population and samples are students in Communication major that are currently enlisted in Gender Communication class, with the total of 49 students. The data collecting technique used in this research is questionnaire. The technique used for data analysis is Quantitative Descriptive. This research concluded that male and female students have significantly different perceptions in terms of Gender Communication. In gendered voices, the male students’ perception was women are more polite than men. Female students’ perception was men uses cursing and insults to develop relations and tends to be more emotional. Regarding bodies, male student’s perception was women are feminine, focuses on physical appearance. On the other hand, female students’ perception on men were having a masculine appearance, taking care of their own appearance, and doesn’t focus too much on their physical appearances. In language, the male students’ perception was women tend to talk more than men because of their richer vocabularies, while female students’ perception was that there was domination in the languages of men